Decision-making under Risk: Evidence from the Hindi Movie Industry. Issue 1 (June 2018) - Ghosh, Soham; Paul, Abhishek; Sharma, Megha; Basu, Sumanta
Despite being the largest producer of movies in the world, Bollywood—the Hindi movie industry—is underresearched. In this article, we first identify the factors that make this industry unique in such a way that research conducted in the context of any other film industry may not be applicable in Bollywood. Using a mix of primary and secondary data, we provide insights into the relationship between various input and output variables. We also identify the major determinants of the satellite right price of a movie and statistically show why the current determinants are far from optimal. We also propose better factors for determining the satellite right price.